Improved 1-year mortality in elderly patients with a hip fracture following integrated orthogeriatric treatment. Issue 1 (January 2017) - Folbert, E.; Hegeman, J.; Vermeer, M.; Regtuijt, E.; Velde, D.; Duis, H.; Slaets, J.
Abstract Summary To improve the quality of care and reduce the healthcare costs of elderly patients with a hip fracture, surgeons and geriatricians collaborated intensively due to the special needs of these patients. After treatment at the Centre for Geriatric Traumatology (CvGT), we found a significant decrease in the 1-year mortality rate in frail elderly patients compared to the historical control patients who were treated with standard care. Introduction The study aimed to evaluate the effect of an orthogeriatric treatment model on elderly patients with a hip fracture on the 1-year mortality rate and identify associated risk factors. Methods This study included patients, aged 70 years and older, who were admitted with a hip fracture and treated in accordance with the integrated orthogeriatric treatment model of the CvGT at the Hospital Group Twente (ZGT) between April 2008 and October 2013. Data registration was carried out by several disciplines using the clinical pathways of the CvGT database. A multivariate logistic regression analysis was used to identify independent risk factors for 1-year mortality. The outcome measures for the 850 patients were compared with those of 535 historical control patients who were managed under standard care between October 2002 and March 2008. Results The analysis demonstrated that the 1-year mortality rate was 23.2 % (n = 197) in the CvGT group compared to 35.1 % (n = 188) in the historical control group (p < 0.001). Independent risk factors for 1-year mortality were male gender (odds ratio (OR) 1.68), increasing age (OR 1.06), higher American Society of Anesthesiologists (ASA) score (ASA 3 OR 2.43, ASA 4–5 OR 7.05), higher Charlson Comorbidity Index (CCI) (CCI 1–2 OR 1.46, CCI 3–4 OR 1.59, CCI 5 OR 2.71), malnutrition (OR 2.01), physical limitations in activities of daily living (OR 2.35), and decreasing Barthel Index (BI) (OR 0.96). Conclusion After integrated orthogeriatric treatment, a significant decrease was seen in the 1-year mortality rate in the frail elderly patients with a hip fracture compared to the historical control patients who were treated with standard care. The most important risk factors for 1-year mortality were male gender, increasing age, malnutrition, physical limitations, increasing BI, and medical conditions. Awareness of risk factors that affect the 1-year mortality can be useful in optimizing care and outcomes. Orthogeriatric treatment should be standard for elderly patients with hip fractures due to the multidimensional needs of these patients.